Clinical Candidates Targeting the ATR-CHK1-WEE1 Axis in Cancer - Gorecki, Lukas; Andrs, Martin; Korabecny, Jan (Cancers, 2021)
Selective killing of cancer cells while sparing healthy ones is the principle of the perfect cancer treatment and the primary aim of many oncologists, molecular biologists, and medicinal chemists. To achieve this goal, it is crucial to understand the molecular mechanisms that distinguish cancer cells from healthy ones. Accordingly, several clinical candidates that use particular mutations in cell-cycle progressions have been developed to kill cancer cells. As the majority of cancer cells have defects in G1 control, targeting the subsequent intra‑S or G2/M checkpoints has also been extensively pursued. This review focuses on clinical candidates that target the kinases involved in intra‑S and G2/M checkpoints, namely, ATR, CHK1, and WEE1 inhibitors. It provides insight into their current status and future perspectives for anticancer treatment. Overall, even though CHK1 inhibitors are still far from clinical establishment, promising accomplishments with ATR and WEE1 inhibitors in phase II trials present a positive outlook for patient survival.
Keywords: DNA damage response; inhibitors; cell-cycle checkpoints; ATR–CHK1–WEE1 axis; clinical trials